Nutritional and cultural conditions for production of poly-3-hydroxybutyric acid byAzotobacter chroococcum - Pal, S; Manna, A; Paul, A K (Folia microbiologica, 1998)
Free-living nitrogen-fixing bacteria have been identified as a potential source of poly-3-hydroxybutyric acid (PHB). Systematic study of this ability of N(2)-fixing organisms has lead to the isolation of an efficient strain, identified asAzotobacter chroococcum. Nutritional requirements and cultural conditions for optimal production of PHB by this strain under laboratory conditions were determined. In N-free liquid medium containing 2% glucose, the strain accumulated PHB up to 68% of its cell dry mass. Glucose and mannitol were found to be the best carbon sources, while organic nitrogen compounds were preferred as nitrogen source. Maximum yield (3.3 g/L) was obtained with 0.2% bactopeptone supplementation. Inorganic phosphate at a concentration suboptimal for growth had some growth-promoting effect. Under oxygen limiting conditions, biomass production was enhanced but a different response was obtained for PHB production.